Reducing the prosthesis modulus by inclusion of an open space lattice improves osteogenic response in a sheep model of extraarticular defect - Reza Sanaei; Charles Neil Pagel; Babatunde A. Ayodele; Bill Lozanovski; Thierry Beths; Martin Leary; Darpan Shidid; Endri Kastrati; Endri Kastrati; Joe Elambasseril; Ulrich Bühner; Tom Williamson; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Stress shielding is a common complication following endoprosthetic reconstruction surgery. The resulting periprosthetic osteopenia often manifests as catastrophic fractures and can significantly limit future treatment options. It has been long known that bone plates with lower elastic moduli are key to reducing the risk of stress shielding in orthopedics. Inclusion of open space lattices in metal endoprostheses is believed to reduce the prosthesis modulus potentially improving stress shielding. However, no in vivo data is currently available to support this assumption in long bone reconstruction. This manuscript aims to address this hypothesis using a sheep model of extraarticular bone defect.Methods: Initially, CT was used to create a virtual resection plan of the distal femoral metaphyses and to custom design endoprostheses specific to each femur. The endoprostheses comprised additively manufactured Ti6Al4V-ELI modules that either had a solid core with a modulus of ∼120 GPa (solid implant group) or an open space lattice core with unit cells that had a modulus of 3–6 GPa (lattice implant group). Osteotomies were performed using computer-assisted navigation followed by implantations. The periprosthetic, interfacial and interstitial regions of interest were evaluated by a combination of micro-CT, back-scattered scanning electron microscopy (BSEM), as well as epifluorescence and brightfield microscopy.Results: In the periprosthetic region, mean pixel intensity (a proxy for tissue mineral density in BSEM) in the caudal cortex was found to be higher in the lattice implant group. This was complemented by BSEM derived porosity being lower in the lattice implant group in both caudal and cranial cortices. In the interfacial and interstitial regions, most pronounced differences were observed in the axial interfacial perimeter where the solid implant group had greater bone coverage. In contrast, the lattice group had a greater coverage in the cranial interfacial region.Conclusion: Our findings suggest that reducing the prosthesis modulus by inclusion of an open-space lattice in its design has a positive effect on bone material and morphological parameters particularly within the periprosthetic regions. Improved mechanics appears to also have a measurable effect on the interfacial osteogenic response and osteointegration.